Circles of support and accountability: The characteristics of core members in England and Wales. (20th May 2016) - Clarke, Martin; Warwick, Leah; Völlm, Birgit
Abstract: Background: Circles of support and accountability, or Circles, use community volunteers to help reintegrate sex offenders at risk of reoffending in the community. Aims: The aims of this study are to describe the first 275 male sex offenders ('core members') in England and Wales supported by a Circle and to compare those attending the five largest Circles. Methods: As part of their monitoring activity, 10 Circles extracted data from case files, anonymised it and submitted it to Circles UK, the national oversight body. Results: Circles have expanded rapidly with 165 (60%) of Circles commencing in the three years 2011–2013 compared with 110 in the nine years 2002–2010. Most core members were referred from the Probation Service (82%). Circles were provided to men with a range of predicted risks of reoffending – from low (26%) to very high (12%). There were some positive changes between the beginning and end of Circles, such as fewer men being unemployed and more living in their own chosen accommodation. Conclusions/implications for practice: Circles have been used to support the reintegration of a wide range of sex offenders. Given their rapid growth and flexibility, consistent recording standards are required across. These standards should be reviewed periodically to ensure all important fields of change are captured, including frequency of attendance, length per session and quality of engagement in the work. Copyright © 2016 John Wiley & Sons, Ltd.